2017
DOI: 10.1002/asi.23985
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of expert survey‐based journal rankings: The role of personal research interests

Abstract: By using the data from two recent survey‐based rankings of knowledge management / intellectual capital and eHealth journals, this study tests the impact of personal research interests of journal raters on their ranking scores. The rationale is that raters assign higher scores to journals that cater to their area of expertise because they are more familiar with them. The results indicate the existence of raters’ bias toward the journals focusing on their preferred areas of interest, but this bias does not unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Second, solely relying on the impact factor to rank journals or, by extension, the quality of an author runs the risk of assuming that only journals with high impact factors are publishing high-quality research and researchers (Adler & Harzing, 2009;Aguinis et al, 2019;Singh, Haddad, & Chow, 2007). Third, as Serenko and Bontis (2018) argued, "It is extremely difficult to deliberately influence the journal quality perceptions of a large group of independent scholars, whereas citations may be dramatically boosted in the short term by means of questionable practices such as forced citations or excessive self-citations" (p. 749). As such, the stated preference approach is considered more suitable for the purposes of our study, since developing a revealed preference journal ranking may not only be difficult to achieve (given the interdisciplinary nature of nonprofit and civil society studies), but it is also not desirable given the well-known limitations of these rankings.…”
Section: Research Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, solely relying on the impact factor to rank journals or, by extension, the quality of an author runs the risk of assuming that only journals with high impact factors are publishing high-quality research and researchers (Adler & Harzing, 2009;Aguinis et al, 2019;Singh, Haddad, & Chow, 2007). Third, as Serenko and Bontis (2018) argued, "It is extremely difficult to deliberately influence the journal quality perceptions of a large group of independent scholars, whereas citations may be dramatically boosted in the short term by means of questionable practices such as forced citations or excessive self-citations" (p. 749). As such, the stated preference approach is considered more suitable for the purposes of our study, since developing a revealed preference journal ranking may not only be difficult to achieve (given the interdisciplinary nature of nonprofit and civil society studies), but it is also not desirable given the well-known limitations of these rankings.…”
Section: Research Approachmentioning
confidence: 99%
“…By inviting nonprofit and civil society scholars to free write journal names instead of presenting them with a predetermined list, we are able to more accurately account for the journal outlets that exist within the field. Indeed, using this approach we are able to capture journals that may not (yet) have an impact factor as well as those that do not aim to achieve one (Serenko & Bontis, 2018). In general, the journals identified in this study are, on average, newer and more specialized in substantive content area than are journals with an impact factor (Adler & Harzig, 2009).…”
Section: Main Takeaways and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult to obtain objective data on corruption, so instead, CPI is created on the basis of expert opinion [3,4]. Although the views of the experts whose input is used for the CPI are based on imperfect information and carry a risk of bias [5][6][7], the resulting index is nonetheless a useful tool to inform the political choices of citizens, guide companies in their investment decisions, and help governments understand how their level of corruption is seen [2,8].…”
Section: Introductionmentioning
confidence: 99%